Vital But Vulnerable: The Population Structure of Macaca maura in Bantimurung Bulusaraung National Park, South Sulawesi - Murti, Warda; Rohman, Fatchur; Saptasari, Murni; Ibrohim, Ibrohim (Bogor Agricultural University, Indonesia, 2026)
Macaca maura is an endemic primate of South Sulawesi, currently listed as Endangered due to habitat fragmentation and increasing anthropogenic pressure. This study aims to analyze the population density, age structure, spatial distribution, and food types consumed by M. maura in the Karaenta Forest, TN Babul. This field study was conducted over four months (August–November 2024) using a grid-based home-range survey. The study area was divided into 1 × 1 km² grid plots; each encounter with M. maura was recorded with X–Y coordinates to visualize the movement patterns of each group. Data were collected through direct observation of eight groups (A–H) with a total of 193 individuals. Group sizes ranged from 13 individuals (Group F) to 39 individuals (Group A). Population density ranged from 52 to 134 individuals/km² with an average of 92 individuals/km². The age distribution, with an average IFR of 0.69, indicates that there is less than one infant per adult female in the M. maura population, suggesting a low reproductive rate. Most individuals were observed on the ground rather than in trees or on cliffs, indicating a preference for terrestrial habitats. Dietary records show considerable flexibility, with 27 plant species being utilized. These findings underscore the need for targeted habitat management strategies aligned with the species' ecological needs. This study provides baseline data to support future evidence-based conservation planning and environmental monitoring of M. maura.